2020
DOI: 10.1016/j.isci.2020.101708
|View full text |Cite
|
Sign up to set email alerts
|

The Chaperone BAG6 Regulates Cellular Homeostasis between Autophagy and Apoptosis by Holding LC3B

Abstract: Summary AMFR/gp78 and USP13 are a pair of ubiquitin ligase and deubiquitinase that ensure the accuracy of endoplasmic reticulum-associated degradation (ERAD). Depletion of USP13 leads to caspase activation and cleavage of the ERAD chaperone BAG6, which is reversed by knockdown of AMFR . However, the mechanism and physiological relevance of this regulation are still unclear. Here, by using the NEDDylator system, we screened out TXN as a substrate of AMFR and USP13 and showed it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…Hence, the deubiquitination action of USP13 eliminates ubiquitin conjugates from Ubl4A to maintain the function of BAB6, thereby ensuring efficient disposal of ERAD substrates. Recently, it was also shown that USP13 and gp78 also regulate the caspase activity of CASP3, which cleaves BAG6 and switches its function from an ERAD regulator to an autophagy tuner [19]. It was shown that the LIR1 motif of BAG6 holds the autophagosome structural membrane proteins LC3B-I and the unprocessed form of LC3B to suppress autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the deubiquitination action of USP13 eliminates ubiquitin conjugates from Ubl4A to maintain the function of BAB6, thereby ensuring efficient disposal of ERAD substrates. Recently, it was also shown that USP13 and gp78 also regulate the caspase activity of CASP3, which cleaves BAG6 and switches its function from an ERAD regulator to an autophagy tuner [19]. It was shown that the LIR1 motif of BAG6 holds the autophagosome structural membrane proteins LC3B-I and the unprocessed form of LC3B to suppress autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…While DUBs localised on the proteasome, such as UCHL5 and USP14 can delay the degradation of proteasomal substrates [17]. Moreover, DUBs are now known to have an important role in ubiquitin chain editing by promoting either K48 ubiquitin conjugates or K63 linked ubiquitin chains on substrates to regulate degradation by the proteasome or via autophagy, respectively [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These include NEDDylation , where fusion of the human NEDD8 (developmentally down-regulated protein 8) E2 ligase Ubiquitin (Ubq)-conjugating 12 (Ubc12) to a POI or small molecule directs addition of Ubq-like NEDD8 to Lys residues of interacting proteins ( Zhuang et al, 2013 ; Hill et al, 2016 ; Chu et al, 2020 ). By adding a His 6 -biotin tag to NEDD8 (HB-NEDD8), which can be biotinylated by BirA ( Zhuang et al, 2013 ) or endogenous biotin ligases ( Chu et al, 2020 ), the NEDD8-tag enables dual affinity purification for increased specificity. Although fast in cell lysates, in vivo NEDDylation may require long labeling times ( Chu et al, 2020 ).…”
Section: Enzyme-based Pl Methodsmentioning
confidence: 99%
“…By adding a His 6 -biotin tag to NEDD8 (HB-NEDD8), which can be biotinylated by BirA ( Zhuang et al, 2013 ) or endogenous biotin ligases ( Chu et al, 2020 ), the NEDD8-tag enables dual affinity purification for increased specificity. Although fast in cell lysates, in vivo NEDDylation may require long labeling times ( Chu et al, 2020 ). Another method, called pupylation-based interaction tagging ( PUP-IT ; Liu et al, 2014 ), employs the promiscuous bacterial prokaryotic Ubq-like protein (Pup) ligase proteasome accessory factor A (PafA) to conjugate the small protein Pup to Lys residues on nearby proteins in the presence of ATP.…”
Section: Enzyme-based Pl Methodsmentioning
confidence: 99%
“…During ER stress, BAG6 is cleaved by caspase 3, leading to its cytoplasmic localization and its interaction with pro-LC3 and LC3-I via the LIR motif (LIR 132−135 ). In this case, BAG6 sequesters LC3-I, preventing autophagosome formation and promoting apoptosis [ 44 ].…”
Section: Bag Family Members In the Regulation Of Autophagy And Select...mentioning
confidence: 99%